Pengaruh Persepsi Manfaat, Kemudahan, Dan Keamanan Terhadap Keputusan Penggunaan Gopay Pada Layanan Gojek - Tanra, Mansyur; Rahman, Rasyid; Rabai, Rahmad; Rajab, Abdul (P3M STIEM, 2022)
This study aims to determine and analyze the effect of (i) perceived benefits on the decision to use gopay, (ii) ease of decision to use gopay, and (iii) security on the decision to use gopay on gojek services. Collecting data using primary data obtained from questionnaires using incidental sampling technique. The population is all 2017 students majoring in management as many as 814 students while the sample taken using the Slovin formula is 89 respondents. The results of the questionnaire have been tested for validity and reliability, and classical assumptions have been tested in the form of normality assumptions, multicollinearity assumptions and heteroscedasticity assumptions. Methods of data analysis using multiple linear regression analysis techniques.The results showed that the perception of benefits had a positive and significant effect on the decision to use gopay with a tcount of 2,220 and a Sig value. 0.029, ease has a positive and significant effect on the decision to use gopay with a tcount of 3,740 and a Sig value. 0.000 and security has a positive and significant effect on the decision to use gopay with a tcount of 2,383 and a sig value. 0.019 on gojek services